Control strategies of domestic electrical storage for reducing electricity peak demand and life cycle cost. (7th December 2016) - Farah, Sleiman; Whaley, David; Saman, Wasim
Abstract: Electricity grid capacity is often oversized to ensure it accommodates maximum anticipated peak demand. In South Australia, 25% of the grid capacity is required for less than 1% of the time. To reflect the cost of peak demand in electricity tariffs, demand tariffs consider not only electrical energy consumption (kWh), but also electrical power demand (kW) during a peak period which is from 16:00–21:00 in South Australia. Demand tariffs increase electricity costs for users needing intermittent electrical energy supply with large electrical peak power demand. To reduce the peak demand and the subsequent electricity cost, batteries are being included in the energy system. In this paper, four control strategies are developed for charging and discharging a battery, and to export and import electricity from the grid. The strategies are simulated with and without a photovoltaic (PV) system using real-time monitored electricity consumption and gross PV generated electricity of a monitored energy-efficient house. The results show that using PV with electrical storage and proper control strategies can reduce both the electricity peak demand and life cycle cost. These results are timely given the recent emergence of small-scale storage technologies and the prediction that these technologies may become commonplace in the near future.